Power Couples: Lawmakers, Lobbyists, and the State of Their Unions - Susan Frelich Appleton; Robyn M. Rimmer (Washington University Journal of Law & Policy, 2007)
Congress has ignored a phenomenon blossoming in its own backyard, the growing number of lawmakers married to lobbyists—unions that we call “power couples” for short. Criticizing government corruption, pundits had raised questions about power couples. One news story asked, “How can a member of Congress possibly share a bed and a bank account with a member of the persuasion industry without a life laced by conflicts of interest?” Frank Clemente, director of Public Citizen’s Congress Watch, ranked the legislator-lobbyist marriage “way up there on the unseemly scale.” Another news report on family lobbying called the phenomenon “an increasingly popular maneuver in the age-old game of influence-seeking in Washington” and observed that today “when a corporation or interest group wants support from a key member of Congress, it often hires a member of the lawmaker’s family.” These ethical issues, in turn, raise theoretical questions about our contemporary understanding of marriage—questions of family law at the heart of this essay. First, some ethics experts identify the problem raised by power couples, put in its most benign form, as one concerning appearances. Given the importance of appearances and a prevailing ethical standard that emphasizes the need to avoid even appearances of impropriety, perceptions of the activities and relationships of legislator-lobbyist spouses necessarily loom large. What does the response to such power couples say about how we conceptualize marriage today? Second, this Essay reveals the importance of taking a closer look at “the state of the unions” in question, specifically the variations among these marriages and the manner in which these couples exercise, use, and share the power colloquially attributed to them. Ultimately, we question the conventional wisdom that the rise of power couples necessarily manifests gender equality in the public sphere. Instead, we suspect that these couples often re-inscribe the traditional stereotype, in which the husband is the preeminent spouse and the wife plays the role of helpmate, and we urge consideration of this issue in any evaluation of the Senate’s action and other possible reforms.
Keywords: Husband & amp; wife; Lobbying; Political ethics; Legislators; U.S. Congress; Capitol Hill; Lobbyists; Marriage